2021
DOI: 10.1021/acsami.1c10428
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Electrically Conductive and Heatable Nanoparticle/Nanocarbon Hybrid Aerogels

Abstract: Joule heating studies on nanoparticle/nanocarbon hybrid aerogels have been reported, but systematic investigations on hydrotalcite-derived catalysts supported onto reduced graphene oxide (rGO) aerogels are rare. In this study, hydrotalcite-derived Cu-Al2O3 nanoparticles were incorporated into a porous and multifunctional rGO aerogel support for fabricating electrically conducting Cu-Al2O3/rGO hybrid aerogels, and their properties were investigated in detail. The hybridization of Cu-Al2O3 with a 3D nanocarbon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In order to construct more continuous heat transfer pathways in a matrix at a lower loading, different types of fillers (two or more) are hybridized and filled into polymer matrices. The common hybridizations include fillers with different particle sizes and fillers with different types or morphologies [ 18 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ].…”
Section: Strategies For Enhancing Thermal Conductivity Of Polymer Com...mentioning
confidence: 99%
“…In order to construct more continuous heat transfer pathways in a matrix at a lower loading, different types of fillers (two or more) are hybridized and filled into polymer matrices. The common hybridizations include fillers with different particle sizes and fillers with different types or morphologies [ 18 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ].…”
Section: Strategies For Enhancing Thermal Conductivity Of Polymer Com...mentioning
confidence: 99%
“…25 Interestingly, nanocarbon aerogels loaded with functional inorganic nanoparticles exhibited no detrimental impacts on the Joule-heating performances. 55 Despite such research efforts, advancements in the Jouleheating performance of nanocarbon aerogels are much less significant than that of nanocarbon films, with the highest reported heating temperature reaching only up to 700 °C. 56 Gaining experimental insights into the factors that impact the electrothermal properties of nanocarbon aerogels is vital for enhancing their Joule-heating performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since the discovery of the Joule-heatable graphene aerogel that can be heated up to 200 °C, at an ultralow voltage of 1 V, with a fast-heating capability of 10 K·s –1 , similar approaches have been adopted in the study of other types of nanocarbon aerogels (e.g., carbon nanotube aerogel, rGO aerogel), resulting in improved heating efficiencies and faster heating kinetics. , Studies on the structure–property relationships of Joule-heatable nanocarbon aerogels showed that high thermal conductivity led to lower Joule-heating efficiency . Interestingly, nanocarbon aerogels loaded with functional inorganic nanoparticles exhibited no detrimental impacts on the Joule-heating performances . Despite such research efforts, advancements in the Joule-heating performance of nanocarbon aerogels are much less significant than that of nanocarbon films, with the highest reported heating temperature reaching only up to 700 °C …”
Section: Introductionmentioning
confidence: 99%
“…The rapid increase in temperature through high-voltage Joule heating followed by rapid cooling provides sufficient energy to overcome kinetic reaction barriers, which helps to achieve nonequilibrium configurations that could surpass the performance of typical catalysts . Here, the high configurational entropy of HEA-NPs helps dissipate the internal stresses to preserve the metastable high-entropy state, which allows taking advantage of the synergistic effects between the constituent elements. , Notably, the nanoparticle composition is easily tunable by simply varying the types and relative amounts of metal salts loaded onto the carbon substrate, making it possible to optimize the multimetallic system for specific catalytic reactions. , …”
mentioning
confidence: 99%
“…18,19 Notably, the nanoparticle composition is easily tunable by simply varying the types and relative amounts of metal salts loaded onto the carbon substrate, making it possible to optimize the multimetallic system for specific catalytic reactions. 20,21 Despite this opportunity, the rapid thermal shock approach faces a number of practical challenges. For one, significantly high temperatures (>1700 °C) are required to produce metal nanoparticles of sufficiently small size.…”
mentioning
confidence: 99%